Dairy Cooperatives in the French Mountains - Daniel Ricard (Revue de Géographie Alpine)
This article analyses dairy cooperatives of the French mountain region by focusing on the following steps: how they are created, how they function, and where they are located. There are three primary types of cooperatives, going back as far as the Middle Ages (in the Jura) and through the 19th century (in Haute-Savoie) to the 20th century, mainly after 1945 (more or less everywhere, but predominantly in the Massif central). Today, there are around 250 dairy cooperatives in the mountain region, mostly in the Jura Mountains. The reason for their survival is their focus on producing quality cheeses protected by an AOC (controlled designation of origin) but also by the actions of the men who have managed this sector. The text underscores the geographical and functional diversity of the movement and examines the notion of mountain cooperatives.